Pengaruh Pemberian Aromaterapi Peppermint terhadap Keluhan Mual Muntah pada Ibu Hamil Trimester I di Wilayah Kerja Puskesmas Pondok Tinggi - Hanifa Zaini. S; Elwitri Silvia; Desni Fitri Halawa (Journal on Education, 2023)
In Indonesia there are (50-90%) cases of nausea and vomiting experienced by pregnant women. The main factor causing maternal death in Indonesia is not nausea and vomiting (emesis gravidarum), but the incidence of nausea and vomiting is quite large, namely (60-80%) in primigravidarum and (40-60%) in multigravida. One hundred in 1000 experience more severe symptoms. The purpose of this study was to determine the effect of giving peppermint aromatherapy to complaints of nausea and vomiting in first trimester pregnant women in the Pondok Tinggi Health Center Working Area in 2022. This research method uses a pre-experimental design using a one group pretest-posttest design. The population in this study was the total number of first trimester pregnant women in the Pondok Tinggi Public Health Center Work Area. Which gets 15 samples. Data were collected using a questionnaire by means of a questionnaire. Data analysis was carried out univariately in the form of frequency distribution and bivariate using T test. The results of the study found that the average score before being given peppermint aromatherapy was (3.20) and before being given peppermint aromatherapy (2.13). Based on the results of statistical tests, there was an effect before being given aromatherapy and before being given peppermint aromatherapy (p-value 0.000). Peppermint aromatherapy has an effect on nausea and vomiting in first trimester pregnant women, it is hoped that first trimester pregnant women can apply peppermint aromatherapy as an alternative to non-pharmacological therapy to overcome nausea and vomiting in first trimester pregnant women.